Soil community richness and composition jointly influence the multifunctionality of soil along the forest-steppe ecotone. (June 2022) - Du, Xiao-Fang; Liu, Han-Wen; Li, Ying-Bin; Li, Bing; Han, Xu; Li, Yu-Hui; Mahamood, Mohammad; Li, Qi
Highlights: Generic richness and composition of soil community jointly influenced soil multifunctionality. The influence of soil community composition on multifunctionality was greater at the regional scale. Microbivores at intermediate trophic level are important for soil multifunctionality. Abstract: Soils harbor an enormous organism which provide multiple ecosystem functions in the terrestrial ecosystem. However, the potential effects of soil biodiversity on soil multifunctionality (multiple ecosystem functions simultaneously provided by soil) have not been investigated thoroughly in terrestrial ecosystems. Along the forest-steppe ecotone, we evaluated the generic richness and composition of bacteria, fungi and nematode communities in meadow steppe, transition zone and birch forest and assessed their relative contributions to soil multifunctionality at both regional and local scales. Our results showed that both richness and community composition of soil organisms played important roles in maintaining soil multifunctionality (multidimensional measure approach). The composition of soil communities on soil multifunctionality was more important at the regional scale (the whole transect) than at the local scale (within individual ecosystem), and the richness of soil organisms could contribute to soil multifunctionality indirectly by changing soil community composition. The richness of bacterivores and fungivores (microbivores) at the intermediate trophic level had the strongest influence on soil multifunctionality suggesting that trophic position of soil organisms was also important in determining soil multifunctionality. Our findings emphasize the importance of assessing the relations of soil biodiversity and ecosystem functions from multitrophic levels, and have important implications for soil biodiversity conservation and management in the forest-steppe ecotone.